Motor biofuel-powered CHP plants—a step towards sustainable development of rural Lithuania - Raslavičius, Laurencas; Strakšas, Anicetas (Technological and Economic Development of Economy, 2011)
This paper focuses on the benefits that can be attained from the correct option of small-scale combined heat and power plant (CHP) relative to fuel availability and sphere of application. The analysis serves as a means of highlighting some of the owners of large-scale farms as well as holders of industrial greenhouses that influence the penetration of small-scale cogeneration plants running on bio-based liquid fuels. The identification of the main influencing factors and their weight is the first step towards the implementation of a more coherent strategy, if the EC (European Commission) and national energy authorities wish for new small-scale cogeneration technologies to have a future in the context of sustainable development of rural Lithuania. Against this background, this paper aims at presenting the technical, environmental and economic aspects of the possibilities of utilizing biodiesel, biodiesel-conventional diesel blends and rapeseed oil in combined heat and power production as an issue for further discussions regarding the formative breakthrough attitude towards a possible path of country's sustainable development.